IMPLEMENTASI MANAJEMEN PENDIDIK DAN TENAGA KEPENDIDIKAN BERBASIS SEKOLAH DALAM PENINGKATAN MUTU SEKOLAH DASAR DI KOTA BEKASI - Karnati, Neti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2017)
The research aims to analyze the implementation of Educator and Education Personnel Management School-Based in improving the quality of Elementary School in the district of North Bekasi.Bekasi City. Quantitative research approach and survey research method. Place of study at State Elementary School in District of North Bekasi. The number of research population is 49 public Elementary School and 35 research samples of public elementary school. The results of the research are: (a) Implementation in the planning needs of Educators and education personnel has been very good, because, as many as 26 schools (74%) are very good, 7 schools (20%) good and 2 schools (6%) enough. (b) Implementation in organizing Educators and Education Personnel Public elementary school has been very good because as many as 23 schools (66%) very good, 12 schools (34%) good. (c) Implementation in the development and development of Primary School Educators and Education Personnel has been very good because, as many as 28 schools (80%) very good, 7 schools (20%). (d) Implementation in the supervision and performance assessment of School Educators and Education Personnel has been very good, because as many as 30 schools (86%) very good, 5 schools (24%) good. (e) Implementation in Dismissal of Primary School Teachers and Education Personnel is good because, as many as 8 schools (23%) very good, 23 schools (65%) good and 4 schools (12%) enough The implication of this research is that the Implementation of Educator and Education Personnel Management public elementary schools that have been very good need to be maintained. The good implementation of Educators and Education Personnel Management can improve their performance increases. The performance of educators and education personnel is expected to improve the quality of education in primary schools. Abstrak Penelitian ini bertujuan untuk menganalisis pelaksanaan Manajemen Pendidik dan Kependidikan Berbasis Sekolah dalam meningkatkan mutu Sekolah Dasar di Kecamatan Bekasi Utara, Kota Bekasi. Pendekatan penelitian kuantitatif dan metode penelitian survei. Tempat studi di Sekolah Dasar Negeri di Kabupaten Bekasi Utara. Jumlah populasi penelitian adalah 49 siswa SD dan 35 sampel penelitian sekolah dasar negeri. Hasil penelitian tersebut adalah: (a) Implementasi dalam perencanaan kebutuhan pendidik dan tenaga kependidikan sudah sangat baik, karena sebanyak 26 sekolah (74%) sangat baik, 7 sekolah (20%) baik dan 2 sekolah (6%) cukup baik. (b) Pelaksanaan pengorganisasian pendidik dan tenaga kependidikan sekolah dasar negeri sudah sangat baik karena sebanyak 23 sekolah (66%) sangat baik, 12 sekolah (34%) baik. (c) Implementasi dalam pengembangan dan pengembangan Pendidik Sekolah Dasar dan Tenaga Kependidikan sudah sangat baik karena, sebanyak 28 sekolah (80%) sangat baik, 7 sekolah (20%) baik. (d) Implementasi dalam supervisi dan penilaian kinerja Pendidik Sekolah dan Tenaga Kependidikan sudah sangat baik, karena sebanyak 30 sekolah (86%) sangat baik, 5 sekolah (24%) baik. (e) Pelaksanaan pemberhentian guru sekolah dasar dan tenaga kependidikan baik karena sebanyak 8 sekolah (23%) memiliki kategori sangat baik, 23 sekolah (65%) baik dan 4 sekolah (12%) cukup . Implikasi dari penelitian ini adalah bahwa implementasi Manajemen Pendidik dan Kependidikan Sekolah Dasar Negeri yang selama ini sangat dibutuhkan harus dijaga. Penerapan Manajemen Pendidik dan Tenaga Kependidikan yang baik dapat meningkatkan kinerja pendidik dan tenaga kependidikan. Kinerja pendidik dan tenaga kependidikan dapat meningkatkan kualitas pendidikan di sekolah dasar.